The Effectiveness of Active Learning Methods in Overcoming Student Learning Boredom In PAK Subject - Telaumbanua, Agus Arda Setiawan; Leiwakabessy, Marchel Anthony; Tampubolon, Martin (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Learning fatigue is a serious challenge in the world of education, including in Christian Religious Education (CRE) subjects. The purpose of this study is to analyze the effectiveness of active learning methods in overcoming learning fatigue among students in CRE subjects. Furthermore, it aims to provide theoretical and practical contributions to the field of basic education, particularly in formulating more adaptive, interactive, and psychologically appropriate learning approaches. This article employs a qualitative research method by analyzing the effectiveness of active learning methods as a solution to address such boredom. Active learning methods, which include strategies such as group discussions, simulations, role-playing, and project-based learning, have proven to increase students' cognitive, emotional, and social engagement. In addition to providing an enjoyable learning experience, this approach also reinforces Christian values in the context of PAK learning. This article concludes that active learning is not only capable of reducing learning boredom but also improving the quality of the learning process holistically. Therefore, teachers need to continuously develop their pedagogical and spiritual competencies to achieve transformative PAK learning that frees students from boredom. This study is expected to serve as a practical reference for teachers and policymakers in designing relevant, interactive, and contextual learning strategies. Moreover, the implementation of active learning methods in CRE subjects can also foster a deeper connection between students and the spiritual teachings of Christianity. By engaging students through hands-on activities such as role-playing biblical stories or collaborating on projects related to Christian values, students are encouraged to actively reflect on their faith in a more meaningful and personal way.